Um estudo de caso de implementação das boas práticas de fabricação em uma empresa de médio porte do setor farmacêutico – dificuldades e recomendações - Fiocchi, Carlos César; Miguel, Paulo Augusto Cauchick (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper aims at demonstrating the difficulties in the implementation of the Good ManufacturingPractices (GMP) standard in a medium-sized pharmaceutical company, according to the requirements. Thiswork outlines the different quality assurance standards with emphasis on the GPM. The research strategy wasbased on a single-case study and the data collection involved document analysis and semi-structuredinterviews. Document records from self-assessments were verified and the company level and evolution werechecked according to the standard. After the data collection, the analysis provided elements to answer theproposed research questions and confirm the evidences of the experienced difficulties to comply with thestandard. The difficulties involved: a lack of more prepared labor, installations not designed according to theGMP, old equipment and an ineffective responsibility definition inside the organization. This paper concludesthat, even with no full compliance with the standard, the company demonstrated to have minimal conditionsto fulfill the standard, allowing for the manufacture of medicines.Keywords: Good Manufacturing Practices; Pharmaceutical Industry; Quality System.